Opportunities and constraints for youth agripreneurs in potato seed multiplication system: Baseline evidence from youth and non-youth in Nakuru County, Kenya - Malit, J.; Kihiu, E.; Gatto, M.; Kirui, L.; Inegbedion, G. (2025)
This report examines opportunities and constraints facing youth agripreneurs in decentralized potato seed multiplication systems in Nakuru County, Kenya. Based on a baseline survey of youth and non-youth seed producers, the study identifies key barriers to youth participation, including limited access to technical support, land, starter materials, and high certification costs, alongside significant pest and disease pressure. While youth are actively engaged in certified seed production (C1–C3), their participation in early-generation seed remains minimal. The findings highlight the need for targeted policies and inclusive extension, land access mechanisms, and capacity development to strengthen youth participation and enhance the resilience and performance of decentralized potato seed systems.